1994
DOI: 10.1128/jvi.68.10.6280-6290.1994
|View full text |Cite
|
Sign up to set email alerts
|

Identification of latency-associated transcripts that map antisense to the ICP4 homolog gene of Marek's disease virus

Abstract: Two small RNAs (0.9 and 0.75 kb), named Marek's disease virus (MDV) small RNAs (MSRs) and a 10-kb RNA, all of which map antisense to the MDV ICP4 homolog gene, have been readily detected in MDCC-MSB1 MDV-transformed T-lymphoblastoid cells. These RNAs were not detectable in reticuloendotheliosis virustransformed T cells. When MDV was reactivated by treatment of lymphoblastoid cells with 25 ,ug of iododeoxyuridine per ml, the relative levels of the transcripts decreased. These RNAs were not detected by Northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…Recently, Gesser et al demonstrated that one can experimentally infect the nodose ganglia following oral infections of mice and that latent infections are readily established there (88,89). In addition, HSV was shown to establish a latent infection in the nodose ganglia and produce gastric ulcers within the stomach in SCID mice (28). These observations shed some light on the etiology of esophageal mucosal disease that is seen in humans with AIDS (316), and it is possible that further studies will demonstrate that HSV plays a role as a direct or underlying factor in other diseases of the gastrointestinal tract.…”
Section: Sites Of Latent Hsv In Humansmentioning
confidence: 99%
“…Recently, Gesser et al demonstrated that one can experimentally infect the nodose ganglia following oral infections of mice and that latent infections are readily established there (88,89). In addition, HSV was shown to establish a latent infection in the nodose ganglia and produce gastric ulcers within the stomach in SCID mice (28). These observations shed some light on the etiology of esophageal mucosal disease that is seen in humans with AIDS (316), and it is possible that further studies will demonstrate that HSV plays a role as a direct or underlying factor in other diseases of the gastrointestinal tract.…”
Section: Sites Of Latent Hsv In Humansmentioning
confidence: 99%
“…The ICP4 homolog is among the alphaherpesvirus gene product homologs that have been identified for MDV (1). Recently, we (11), and others (22,23) have identified a group of latencyrelated RNAs which map antisense to the MDV ICP4 gene. The latency-related RNAs reported so far include two small, spliced RNAs termed MDV small RNAs (MSRs) (11).…”
mentioning
confidence: 99%
“…Recently, we (11), and others (22,23) have identified a group of latencyrelated RNAs which map antisense to the MDV ICP4 gene. The latency-related RNAs reported so far include two small, spliced RNAs termed MDV small RNAs (MSRs) (11). The difference between the MSRs is unknown; therefore, in this report, the two MSR species will be discussed together and considered equivalent.…”
mentioning
confidence: 99%
“…In latently infected lymphocytes there are less than five copies of viral DNA, and latency-associated transcripts are present in the form of a group of RNAs which map antisense to the homologue of the herpes simplex virus (HSV) ICP4 gene (Li et al 1994;Cantello et al 1994).…”
Section: (C) Pathogenesismentioning
confidence: 99%
“…An MDV gene homologous to the ICP4 gene of HSV has been mapped to the inverted repeat flanking the unique short region of the MDV genome (figure 3) (Anderson et al 1992). This gene is of interest because transcripts which map antisense to the ICP4 homologue gene are found in lymphoblastoid cell lines and lymphomas and sense transcripts in lytic MDV infections (table 2) (Li et al 1994;Cantello et al 1994). It has been suggested that the antisense transcripts are latency-associated transcripts and therefore involved in the transformation process as latency is a prerequisite for oncogenesis and maintenance of the transformed state.…”
Section: (F ) Infected Cell Protein 4 (Icp4) Genementioning
confidence: 99%